A Century of Experimentation: Institutional Approaches to Knowledge Production in Russia from 1917 to 2017 and Their Implications for IP and Competition Equilibrium. (December 2017) - Ivanov, Alexey; Voinikanis, Elena
The Soviet system of knowledge production based on cooperation, knowledge sharing, but also intense competition was already an inspiration for innovation policymakers in the U.S. and in Europe back in the 1950 and 1960s. Nowadays, as the global economy is moving towards a new mode of production, the Soviet case may still play an important role to help to frame a better institutional approach to innovation. With the dramatic challenges already brought by the fourth industrial revolution and the tectonic economic and social shifts it is expected to cause around the world, the Soviet case with all its pros and cons is becoming more and more relevant for this debate as it provides necessary empirical data to consider other institutional approaches to innovation distinct from the established property-focused model. In this context, intellectual property and competition law scholars hopefully would better understand the Soviet innovation system through further academic studies.